Engklek as a Social Space: Social Interaction of Children with Special Needs in Inclusive Early Childhood Education - Alif Laini; Nur Fitriyanti; Sofia Yunus Putri; Sutiyah Nova Irawati; Andi Cahyuni Candrawati (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2026)
This study examines the process of social interaction among children with special needs in the traditional Engklek game within inclusive early childhood education. Using a qualitative case study design, data were collected through participant observation, teacher interviews, and documentation, and analyzed using Braun and Clarke’s thematic analysis. Findings reveal that social interaction develops progressively from individual play to cooperative engagement, marked by increased communication, collaboration, and participation. Communication occurs multimodally, both verbal and non-verbal, while cooperation is reflected in turn-taking, peer assistance, and simple conflict resolution. Teachers play a crucial role as facilitators and social mediators, shaping interaction quality through stimuli provision, group management, and appropriate interventions. The study highlights that Engklek serves not only as a learning medium but also as a social space where children develop social skills through meaningful interaction. It contributes by shifting the perspective from outcome-based to process-based approaches in studying traditional games and offers practical implications for play-based inclusive learning in early childhood education.